Electroencephalogram-Based Brain Connectivity Analysis in Prolonged Disorders of Consciousness - Yuzhang Wu; Zhitao Li; Ruowei Qu; Yangang Wang; Zhongzhen Li; Le Wang; Guangrui Zhao; Keke Feng; Yifeng Cheng; Shaoya Yin (Neural Plasticity)
Background. Prolonged disorders of consciousness (pDOC) are common in neurology and place a heavy burden on families and society. This study is aimed at investigating the characteristics of brain connectivity in patients with pDOC based on quantitative EEG (qEEG) and extending a new direction for the evaluation of pDOC. Methods. Participants were divided into a control group (CG) and a DOC group by the presence or absence of pDOC. Participants underwent magnetic resonance imaging (MRI) T1 three-dimensional magnetization with a prepared rapid acquisition gradient echo (3D-T1-MPRAGE) sequence, and video EEG data were collected. After calculating the power spectrum by EEG data analysis tool, DTABR (δ+θ/α+β ratio), Pearson’s correlation coefficient (Pearson r), Granger’s causality, and phase transfer entropy (PTE), we performed statistical analysis between two groups. Finally, receiver operating characteristic (ROC) curves of connectivity metrics were made. Results. The proportion of power in frontal, central, parietal, and temporal regions in the DOC group was lower than that in the CG. The percentage of delta power in the DOC group was significantly higher than that in the CG, the DTABR in the DOC group was higher than that in the CG, and the value was inverted. The Pearson r of the DOC group was higher than that of CG. The Pearson r of the delta band (Z=−6.71, P<0.01), theta band (Z=−15.06, P<0.01), and alpha band (Z=−28.45, P<0.01) were statistically significant. Granger causality showed that the intensity of directed connections between the two hemispheres in the DOC group at the same threshold was significantly reduced (Z=−82.43, P<0.01). The PTE of each frequency band in the DOC group was lower than that in the CG. The PTE of the delta band (Z=−42.68, P<0.01), theta band (Z=−56.79, P<0.01), the alpha band (Z=−35.11, P<0.01), and beta band (Z=−63.74, P<0.01) had statistical significance. Conclusion. Brain connectivity analysis based on EEG has the advantages of being noninvasive, convenient, and bedside. The Pearson r of DTABR, delta, theta, and alpha bands, Granger’s causality, and PTE of the delta, theta, alpha, and beta bands can be used as biological markers to distinguish between pDOC and healthy people, especially when behavior evaluation is difficult or ambiguous; it can supplement clinical diagnosis.